Unveiling Epistemological Perspectives in Software Effort Estimation: A Comprehensive Tertiary Study - Jayadi, Puguh; Patmanthara, Syaad (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
The research examined epistemology in Software Effort Estimation (SEE), focusing on the evaluation methods and metrics used. Accurate estimation of effort is essential to the success of a software project. This study also aims to understand the various methods applied in SEE and how evaluation metrics are applied in this context. The proposed method in the study is to review the Systematic Literature Review (SLR) paper to analyze articles published in reputable international journals. The experimental methodology involves the identification, selection, and in-depth analysis of relevant studies, emphasizing the quality and relevance of existing research. The results show that although many methods are available, the proper selection is still challenging for researchers and practitioners alike. In addition, diverse evaluation metrics reflect the need for a more empirical approach to assessing the effectiveness of applied methods. The conclusions of this study provide significant insights for SEE practice and open up opportunities for further research in this area.